Author Correction: Biocementation mediated by native microbes from Brahmaputra riverbank for mitigation of soil erodibility - Dubey, A.A.; Ravi, K.; Mukherjee, A.; Sahoo, L.; Abiala, M.A.; Dhami, Navdeep (2021)
The original version of this Article contained an error in Figure 4, where Figure 4d was a duplication of Figure 4e. The original Figure 4 and accompanying legend appear below. In addition, in Table 1, in the column “Properties”, “Clay content % (≤ 0.075 mm)”. now reads: “Clay content % (≤ 0.002 mm)”. The original Article has been corrected.